Estudo teórico da interação entre oxigênio molecular e clusters bimetálicos de AuCu e Au-Ag - SILVA, Augusto Cesar Azevedo (2017)
In this work the theoretical study of the bimetallic clusters of Au-Ag and Au-Cu was carried out, in which such clusters were determined by the addition of Ag and Cu atoms in pure structures of Au clusters, through the GA-DFT joint methodology. The AuCu and Au-Ag structures were described in a classical way using the Gupta potential via the genetic algorithm. The lower energy structures were optimized via DFT using the PBE functional through the SIESTA 3.2 program package. The most stable clusters were those with 13 atoms for Au-Ag bimetallic clusters, Au-Cu bimetallic clusters stabilized with 13, 15 and 20 atoms. Both clusters have a degree of aromaticity, more pronounced in the AuAg atoms, than in the Au-Cu atoms. The Au-Ag clusters adsorb the oxygen more favorably in end-on or bridge, whereas the bimetallic clusters of Au-Cu adsorb the molecular oxygen generally according to the bridge or double bridge model. The adsorption of oxygen in bimetallic clusters is intrinsically related to the ability of oxygen to perform π backdonation for the metallic atoms in the cluster.